Magnitude of the benefit of progression-free survival as a potential surrogate marker in phase 3 trials assessing targeted agents in molecularly selected patients with advanced non-small cell lung cancer: systematic review. - Katsuyuki Hotta; Yuka Kato; Natasha Leighl; Nagio Takigawa; Rabab Mohamed Gaafar; Hiroe Kayatani; Taizo Hirata; Kadoaki Ohashi; Toshio Kubo; Masahiro Tabata; Mitsune Tanimoto; Katsuyuki Kiura (PLoS ONE)
Background In evaluation of the clinical benefit of a new targeted agent in a phase 3 trial enrolling molecularly selected patients with advanced non-small cell lung cancer (NSCLC), overall survival (OS) as an endpoint seems to be of limited use because of a high level of treatment crossover for ethical reasons. A more efficient and useful indicator for assessing efficacy is needed. Methods and findings We identified 18 phase 3 trials in the literature investigating EGFR-tyrosine kinase inhibitor (TKIs) or ALK-TKIs, now approved for use to treat NSCLC, compared with standard cytotoxic chemotherapy (eight trials were performed in molecularly selected patients and ten using an "all-comer" design). Receiver operating characteristic analysis was used to identify the best threshold by which to divide the groups. Although trials enrolling molecularly selected patients and all-comer trials had similar OS-hazard ratios (OS-HRs) (0.99 vs. 1.04), the former exhibited greater progression-free survival-hazard ratios (PFS-HR) (mean, 0.40 vs. 1.01; P<0.01). A PFS-HR of 0.60 successfully distinguished between the two types of trials (sensitivity 100%, specificity 100%). The odds ratio for overall response was higher in trials with molecularly selected patients than in all-comer trials (mean: 6.10 vs. 1.64; P<0.01). An odds ratio of 3.40 for response afforded a sensitivity of 88% and a specificity of 90%. Conclusion The notably enhanced PFS benefit was quite specific to trials with molecularly selected patients. A PFS-HR cutoff of ∼0.6 may help detect clinical benefit of molecular targeted agents in which OS is of limited use, although desired threshold might differ in an individual trial.